2013
DOI: 10.1097/wnf.0b013e31827db49b
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Pharmacology of a Single Intravenous Dose of Ponezumab in Subjects With Mild-to-Moderate Alzheimer Disease

Abstract: A 2-hour infusion of 0.1 to 10 mg/kg ponezumab was well tolerated in subjects with mild-to-moderate AD. Plasma pharmacokinetic profile was approximately linear. Plasma Aβ increased with dose, and CSF Aβ increased at the highest dose, suggesting that intravenous ponezumab alters central Aβ levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 16 publications
0
53
0
2
Order By: Relevance
“…In related studies, it is surprising how limited PK/PD data have been presented for the Ab immunotherapy trials. The most detailed PK/PD study for a CNS therapeutic antibody to date was for Ponezumab, and indicated that its CNS concentration was approximately 0.1% of peripheral exposure [4,90]. Data from microdialysis studies in P301S mice…”
Section: Mechanism Of Anti-tau Immunotherapymentioning
confidence: 99%
“…In related studies, it is surprising how limited PK/PD data have been presented for the Ab immunotherapy trials. The most detailed PK/PD study for a CNS therapeutic antibody to date was for Ponezumab, and indicated that its CNS concentration was approximately 0.1% of peripheral exposure [4,90]. Data from microdialysis studies in P301S mice…”
Section: Mechanism Of Anti-tau Immunotherapymentioning
confidence: 99%
“…Following these encouraging studies in mice, a phase I clinical trials was initiated. Reportedly, Ponezumab increased plasma and CSF Aβ 40 levels in a dose dependent fashion with minimal adverse effects (Burstein et al 2013; Landen et al 2013). Similarly, a phase II trial demonstrated increased plasma Aβ 40 levels with good tolerance.…”
Section: Passive Immunization Targeting Aβmentioning
confidence: 99%
“…Ponezumab (PF-04360365) is a humanized IgG2δA monoclonal antibody that unlike the other monoclonal antibodies binds the free carboxyl terminal of amino acids 33-40 of the Aβ 1-40 peptide (72). Five phase I trials showed acceptable safety but two phase II trials concluded in 2011 showed no treatment effect and development of ponezumab for AD is no longer being pursued although its use is being explored in patients with cerebral amyloid angiopathy.…”
Section: Passive Immunotherapymentioning
confidence: 99%